Subsets of CD1c+ DCs: Dendritic Cell Versus Monocyte Lineage - Heger, Lukas; Hofer, Thomas P.; Bigley, Venetia; de Vries, I. Jolanda M.; Dalod, Marc; Dudziak, Diana; Ziegler-Heitbrock, Loems (Frontiers in Immunology, 2020)
Currently three bona fide dendritic cell (DC) types are distinguished in human blood. Herein we focus on type 2 DCs (DC2s) and compare the three defining markers CD1c, CD172 and CD301. Using CD1c to define DC2s, a CD14+ and a CD14- subset can be detected. The CD14+ subset shares features with monocytes and this includes substantially higher expression levels for MAFB, S100A8/9, CD163 and Ficolin1. We review the current knowledge of these CD1c+ CD14+ cells as compared to the CD1c+ CD14- cells with respect to phenotype, function, transcriptomics and ontogeny. Here, we discuss informative mutations, which suggest that two populations have different developmental requirements. In addition, we cover subsets of CD11c+CD8- DC2s in the mouse, where CLEC12A+ESAMlow cells, as compared to the CLEC12A-ESAMhigh subset, also express higher levels of monocyte-associated markers lysozyme, CD14 and CD36. Finally, we summarize, for both man and mouse, the data on lower antigen presentation and higher cytokine production in the monocyte-marker expressing DC2 subset, which demonstrate that the DC2 subsets are also functionally distinct.